Lyubovta na Shubert - Stanoeva, R
Line art of man and woman in evening dress, and Schubert, amid flower illustrations Poster advertising musical performance of Franz Schubert's works, held at the National Music Theatre Stefan Makedonski, Sofia. Original title: Любовта на Шуберт PO-1074